2014
DOI: 10.1021/am502736m
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Polymer-Skinned Electroactive Materials of Lithium-Ion Batteries: Ready for Monocomponent Electrodes without Additional Binders and Conductive Agents

Abstract: Rapid growth of mobile and even wearable electronics is in pursuit of high-energy-density lithium-ion batteries. One simple and facile way to achieve this goal is the elimination of nonelectroactive components of electrodes such as binders and conductive agents. Here, we present a new concept of monocomponent electrodes comprising solely electroactive materials that are wrapped with an insignificant amount (less than 0.4 wt %) of conducting polymer (PEDOT:PSS or poly(3,4-ethylenedioxythiophene) doped with poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 40 publications
1
64
0
Order By: Relevance
“…Conducting polymer coating is also reported as another strategy, which not only be able to protect the surface of cathode, but also to serve as a conductive matrix. Compounds such as aniline [17,18], pyrrole [19,20], 3,4-ethylenedioxythiophene [21,22], acrylonitrile [23] [24]. Employing monomer units of conducting polymers as electrolyte additives is a more economic and effective way to in-situ coat the electrode [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Conducting polymer coating is also reported as another strategy, which not only be able to protect the surface of cathode, but also to serve as a conductive matrix. Compounds such as aniline [17,18], pyrrole [19,20], 3,4-ethylenedioxythiophene [21,22], acrylonitrile [23] [24]. Employing monomer units of conducting polymers as electrolyte additives is a more economic and effective way to in-situ coat the electrode [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Additional improvement of the electrochemical properties of LFP-based cathode materials with the use of conducting polymer coatings [9][10][11][12][13][14][15][16][17][18][19][20], and in particular, poly-3,4-ethylenedioxythiopene [12,[13][14][15] was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Very high specific capacitance and good high-rate capability of electrode material has been achieved by synthesis of PPy/CNT composite with controlled pore size in a three-dimensional entangled structure of a CNT film using an electrostatic spray deposition process [112]. Recently, Paul et al synthesized polypyrrole (PPy) / multi-walled carbon nanotube (MWCNT) / conductive carbon (CC) composites by chemical oxidative polymerization method using anhydrous FeCl 3 . The impedance behavior of PPy / MWCNT / CC electrodes in their insulating state, have been taken before and after performed chargingdischarging 500 cycles in the potential range from 0 to 0.6 V. Charge transfer resistance, R ct , of composites comprising 10, 15 and 20 wt% of MWCNT determined before cycling processes have shown values of 7.4, 2.1 and 4.3 respectively, which indicated that only optimal amount of MWCNT could facilitate the charge transfer throughout the system [113].…”
Section: Electrochemical Properties Of Ppy Based Compositesmentioning
confidence: 99%
“…One of the most interesting materials of this kind are electroconducting polymer materials (ECP) regarding the possibility of reversible change of their reduced (insulating) and oxidized (conducting) state by the means of the processes of reduction (undoping) and oxidation (doping). This feature, offers very broad application areas of electroconducting polymer materials, as electrodes in rechargeable batteries [1], electrochemical capacitors (supercapacitors) [2,3], sensors [4], actuators [5], solar cells [6], selective gas membranes [7], in the corrosion protection [8,9], and even in the field of drug delivery [10] and tissue engineering systems [11]. The interest for electroconducting materials (ECM) in general started back in the '70s of the last century by the discovery of changes in the electroconducting properties of polyacetylene, firstly synthesized in 1958, by its treatment with oxidizing agent, e.g.…”
Section: Introductionmentioning
confidence: 99%